Pollinator Insect Found in Coconut Tree in Banyuasin Regency, South Sumatera - Erise Anggraini; Tia Ellisa Riyanti; Chandra Irsan; Harman Hamidson; Marlin Sefrilla; Astuti Kurnianingsih; Wei Hong Lau; Mahesh Tiran Gunasena (Andalasian International Journal of Entomology, 2023)
Insect pollinators are insects that play an important role in maintaining the existence of a plant species through pollination and maintaining the genetic diversity of plants in the population maintaining the existence of a plant species through pollination and maintaining the genetic diversity of plants in the population. Pollinator insects generally come from the Hymenoptera order. The purpose of this study was to determine the types of pollinator insect species that dominate coconut plantations in the Banyuasin area of South Sumatra. Data were collected by field observation using the plant survey method. The survey was conducted through direct observation of coconut plants owned by coconut farmers in the Banyuasin area. Observations were made on coconut plants by observing pollinator insect species that associate with flowers on coconut plants. Insect pollinator species found in coconut plantations in the Banyuasin area include Vespa affilish, Apis mellifera, and Apis dorsata. The most dominant type of pollinator insect found in coconut plantations in the Banyuasin area is Apis dorsata with 201 individuals. So, the results show that the abundance of individuals is high but has a low diversity index.